2020
DOI: 10.1021/acs.energyfuels.0c02902
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Precipitation Modes of Paraffin Wax in Water-in-Model-Oil Emulsions

Abstract: The precipitation of wax crystals in water-in-crude-oil emulsion impairs the safety and economy of multiphase transportation in oil fields. At present, there are different opinions on the precipitation modes of paraffin wax. Existing studies mostly use microscopic observation to determine whether wax crystals are adsorbed at the oil−water interface. In this study, the precipitation modes of paraffin wax in water-in-model-oil emulsions were comprehensively investigated by combining calorimetry, drop shape analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…According to previous studies, the viscosity, gel temperature, and yield stress , of waxy oil emulsion was increased in contrast with those of waxy oil. The added water cut changed the original structure of the waxy oil, where the precipitated wax crystals connected with water droplets through interfacial adsorption , and/or enveloped small water droplets to the inside of the wax crystal network, forming a wax crystal-water droplet aggregation that is shown in Figure . The liquid oil phase with the other components, such resin and asphaltene, was also entrapped at the inner space of the aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, the viscosity, gel temperature, and yield stress , of waxy oil emulsion was increased in contrast with those of waxy oil. The added water cut changed the original structure of the waxy oil, where the precipitated wax crystals connected with water droplets through interfacial adsorption , and/or enveloped small water droplets to the inside of the wax crystal network, forming a wax crystal-water droplet aggregation that is shown in Figure . The liquid oil phase with the other components, such resin and asphaltene, was also entrapped at the inner space of the aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…If the wax molecules cannot cocrystallize with the emulsifier, the wax molecules will not crystallize at the water droplet interface. Li et al showed that wax crystals not only precipitate in the oil phase but also precipitate and adsorb at the oil–water interface and force the interface to solidify, resulting in wrinkling of the interface as it shrinks and a more viscoelastic gelling structure of the emulsion. It has also been suggested in the literature that water droplets provide the necessary nucleation sites for the crystalline precipitation of wax molecules, thus making them precipitate more easily …”
Section: Wax: Structures and Thermodynamic And Phase Behaviorsmentioning
confidence: 99%
“…This stability depends greatly on the interaction between water droplet fillers and fat/wax crystals dispersed in the continuous oil phase . These crystals either aggregate as a spatial network that physically encloses the water droplets, thereby preventing droplet collisions, , and/or are modified by an emulsifier as an interfacial attaching species to create a solid shell around individual water droplets, thereby hindering the contact, flocculation, and coalescence of droplets. The stability of the emulsion is maintained by these two mechanisms . Moreover, there are two kinds of interfacial attachment.…”
Section: Introductionmentioning
confidence: 99%